1993
DOI: 10.1002/cber.19931260132
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced [2 + 2] Cycloaddition of 2‐Morpholinoacrylonitrile to 1‐Naphthalenecarbonitrile

Abstract: Photoexcited 1‐naphthalenecarbonitrile (1) adds 2‐morpholinoacrylonitrile (2) in the [2 + 2] mode both at the C(1) – C(2) and C(7) – C(8) bond unidirectionally and with the formation of only one (3 and 4, respectively) of the two a priori possible stereoisomers in each case. The structure of 3 has been unambiguously confirmed by an X‐ray structural analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Our previous finding that 1-naphthonitrile (5), when excited in the presence of 2, does not give rise to any 1,4-adduct, instead the two cyclobutanaphthalenes 6 and 7 were formed, 12 is in analogy to related cases in the literature 10,11 (Scheme 2). …”
Section: Methodssupporting
confidence: 53%
“…Our previous finding that 1-naphthonitrile (5), when excited in the presence of 2, does not give rise to any 1,4-adduct, instead the two cyclobutanaphthalenes 6 and 7 were formed, 12 is in analogy to related cases in the literature 10,11 (Scheme 2). …”
Section: Methodssupporting
confidence: 53%
“…63,64 In the same study, the intramolecular mode was shown to also give cycloadduct isomers 81 and 82, in a 20:1 ratio (unfortunately, no chemical yield was provided) (Scheme 23). Dopp et al 65 studied the reaction of cyanonaphthalene with 1,1-disubstituted olefins. Monosubstituted naphthalenes also underwent intramolecular cycloaddition with enol ethers, but the position of the tether had a strong influence on reactivity.…”
Section: Ortho Cycloaddition With Polycyclic Aromaticsmentioning
confidence: 81%
“…Dopp et al 65 studied the reaction of cyanonaphthalene with 1,1-disubstituted olefins. Monosubstituted naphthalenes also underwent intramolecular cycloaddition with enol ethers, but the 66 Depending on the substituent, various ratios of ortho and para products were obtained, and a triplet biradical mechanism was proposed.…”
Section: Ortho Cycloaddition With Polycyclic Aromaticsmentioning
confidence: 99%
“…Reversible [2 + 2] photocycloaddition leading to 99 was observed. 82 Independently, the biradical intermediate 100 was formed, also in a reversible photochemical reaction. 83 Only the latter intermediate leads to the formation of stable final products.…”
Section: Photocycloadditions With Condensed Aromatic Compoundsmentioning
confidence: 99%
“…In the case of R = 2,5-di t Bu, the corresponding compound 79 is formed in high yields and no side product was detected. Products 80 are formed by an initial [2 + 4] cycloaddition involving the carbonyl π-bond of the aldehyde function and one π-bond of the aromatic moiety (82). It must, however, be pointed out that these reactions are most probably not concerted.…”
Section: The [2 + 3] or Meta Photocycloadditionmentioning
confidence: 99%